Intimate partner homicide: Comparison between homicide and homicide-suicide in Portugal - Gonçalves, Mariana (2024)
Intimate partner homicide (IPH) is a tragic event. Studies involving the comparison between IPH and intimate partner homicide-suicide (IPH-S) are scarce, with few studies in Portugal about this issue. The current study aims to compare IPH and IPH-S perpetrators, the victim–perpetrator relationships dynamics, and homicide circumstances. The data was collected through the analysis of 78 judicial processes of IPH that occurred in Portugal, between 2010 and 2015. Of the cases, 51 were IPH, 20 were IPH-S cases, and seven were attempted suicide cases, being perpetrated in 84.6% (n = 66) for male perpetrators. Suicide after intimate homicide were all committed by men. All judicial processes analyzed refer to heterosexual relationships. Bivariate and multivariate analyses were performed to compare the groups concerning perpetrator and victim sociodemographic characteristics, victim-perpetrator dyadic dynamics, and crime circumstances. The results show mostly common trends between the two groups with some differentiating factors when compared individually (e.g., perpetrator professional status, criminal records). Regression logistic analysis showed no differences between IPH and IPH-S.